If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(x) = 5x + -5 Multiply m * x mx = 5x + -5 Reorder the terms: mx = -5 + 5x Solving mx = -5 + 5x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by 'x'. m = -5x-1 + 5 Simplifying m = -5x-1 + 5 Reorder the terms: m = 5 + -5x-1
| -4x+-36=-8 | | (x)=5x-5 | | 4(5y-3)-3=5 | | 8w-2=-10w-30+4 | | 33b-24b-7+24=-5 | | 46x-25y=15 | | 20y-12-3y=5 | | 2t-5=18.8 | | (3x^2+11+20)+(10x^2-21x-3)= | | (6+R)+2=2(R+2) | | 497= | | -9+8r=7(-5r-1)-2 | | 6u=21-4 | | 29p-3=45 | | 1100+600+5x=700+400+8x | | 4t-13=7 | | 8x-3y=-121 | | 10x-10=3x+11 | | 5(x+5)(2x+1)=110 | | -126=7x-7(2x+11) | | 18p-3=11p-45 | | 2(x-8)+10=7x+39 | | 7+8g=55 | | 0+8n=8n | | 2(5x+2)=3x^2-10x-28 | | 0+8n=82 | | -120=4b | | -4.5-5.8= | | 12x^3+20x^2-x-6=0 | | 27+k=56 | | (x^2-5)(2x^2+3)= | | 9f+7=8f |